2022
DOI: 10.3389/fgene.2022.801484
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Immune-Related Prognostic Signatures in the Tumor Microenvironment of Colon Cancer

Abstract: Background: Colon cancer is a common malignant tumor with poor prognosis. The aim of this study is to explore the immune-related prognostic signatures and the tumor immune microenvironment of colon cancer.Methods: The mRNA expression data of TCGA-COAD from the UCSC Xena platform and the list of immune-related genes (IRGs) from the ImmPort database were used to identify immune-related differentially expressed genes (DEGs). Then, we constructed an immune-related risk score prognostic model and validated its pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…In China, about 95% of GC patients have the characteristics of microsatellite stability (MSS) (61). Patients with GC in the MSI-H group had a higher survival rate and significantly more benefit from immunotherapy in contrast to the MSS/MSI-L group (62,63). Consistently, according to our research, the high-NRGPS group of GC patients had a larger percentage of MSS and a lower percentage of MSI-H.…”
Section: Discussionsupporting
confidence: 82%
“…In China, about 95% of GC patients have the characteristics of microsatellite stability (MSS) (61). Patients with GC in the MSI-H group had a higher survival rate and significantly more benefit from immunotherapy in contrast to the MSS/MSI-L group (62,63). Consistently, according to our research, the high-NRGPS group of GC patients had a larger percentage of MSS and a lower percentage of MSI-H.…”
Section: Discussionsupporting
confidence: 82%
“…Patients with GC in the MSI-H group had higher survival rates than patients in the MSS or low-MSI groups ( Zhang et al, 2022 ). In patients with colon cancer, it was found that patients in the MSI-H group benefited significantly more from immunotherapy than patients in the MSS or MSI-L groups ( Cao et al, 2022 ). Our study found that patients with GC in the high-PRFGPS subgroup had a higher proportion of MSS and a lower proportion of MSI-H.…”
Section: Discussionmentioning
confidence: 99%
“…[287][288][289][290][291] A positive correlation between EMT and immune checkpoint proteins was identified in multiple cancer types, including lung, breast, colorectum, oral, and esophageal cancers, 289,292-297 and a higher expression of these checkpoint molecules indicates worse prognosis in a broad range of cancers. [298][299][300] The functional relationship between immune checkpoint proteins and therapy evasion suggests that a combination treatment with immune checkpoint blockade (ICB) could be promising in developing a new approach against TCP.…”
Section: With Immune Checkpoint Blockade (Icb)mentioning
confidence: 99%